Effects of ciprofol on postoperative delirium and outcomes in older patients undergoing major thoracic surgery: protocol for a multicentre, prospective, single-blinded, randomised controlled study - Li Wang; Hao Wang; Ailin Luo; Qian Liu; Wei Xiao; E Wang; Xiaoping Gu; Wen Ouyang; Tianlong Wang; Pu Hong; Shibiao Chen (BMJ Open)
Introduction Postoperative delirium (POD) is a notable complication in older adults undergoing major thoracic surgery and is associated with poor clinical outcomes. Ciprofol, an innovative sedative known for its haemodynamic stability, holds the potential to lower the risk of POD. However, high-quality evidence supporting this claim is limited. The objective of this study is to evaluate the effect of ciprofol compared with propofol on the incidence of POD and postoperative outcomes in older patients undergoing thoracic surgeries.Methods and analysis This multicentre, prospective, single-blinded, randomised controlled trial will recruit patients aged ≥65 years scheduled for elective thoracoscopic lobectomy or segmentectomy, with an anticipated anaesthesia duration of at least 2 hours. Participants will be randomised to receive either ciprofol (0.25–1.5 mg/kg/hour) or propofol (1–6 mg/kg/hour) in a 1:1 ratio. The primary outcome is the incidence of POD within 7 days postoperatively, assessed via the three-dimensional confusion assessment method. Secondary outcomes include emergence delirium assessed using the confusion assessment method for the intensive care unit, the incidence of combined adverse events during induction and maintenance of anaesthesia, duration of intraoperative hypotension, minimum mean intraoperative arterial pressure, duration of Wavelet Index <40, other adverse events identified during the follow-up period, length of stay, first exhaust time and postoperative first time to taking food. A non-inferiority margin of 5% is applied for sample size calculation, yielding a total of 214 participants, adjusted for a 10% attrition rate.Ethics and dissemination Approval on ethical grounds has been received from the ethics committee of Xuanwu Hospital, Capital Medical University (LinYanShen (2024)-NO.201–003-Revised V.1). We will publish the findings in peer-reviewed journals.Trial registration number NCT06674226.